Entomofauna resource distribution associated with pig cadavers in Bogotá DC (2011)
A cadaver represents a temporal energy-loaded resource, which provides arthropods with food, protection and a place in which to find a mate. Insects are usually the first organisms to discover and colonize a cadaver; as decomposition progresses, insects colonize cadavers in a predictable sequence. This work aimed to establish cadaverous entomofauna relationships with regard to stages of decomposition and environmental conditions using multiple correspondence analysis and thereby to identify the way in which insects distribute a perishable and changing resource. Entomofauna were thus collected in a semi-rural area near Bogotá from the cadavers of three pigs (Sus scrofa L.) which had been shot. Environmental variables were recorded for each sampling. Multiple correspondence analyses were carried out for adult forms belonging to Diptera and Coleoptera families and stages of decomposition, and for Diptera and Coleoptera adult forms and environmental conditions. Stages of decomposition were a primary determining factor for structuring four guilds of entomofauna. However, environmental conditions influenced insect activity and were therefore a relevant factor in the structure of the entomofauna community. The results showed that the insects' distribution of available resources was related to changes in the stage of decomposition. © 2010 The Authors. Medical and Veterinary Entomology © 2010 The Royal Entomological Society.